Biofilm formation of a bacterial consortium on linuron at micropollutant concentrations in continuous flow chambers and the impact of dissolved organic matter. Issue 1 (5th February 2014) - Horemans, Benjamin; Hofkens, Johan; Smolders, Erik; Springael, Dirk
Abstract Bacterial multispecies biofilms are catalysts for pollutant degradation in aqueous ecosystems. Their activity in systems where xenobiotics occur as micropollutants (μg L−1 level) and natural dissolved organic matter provides carbon and energy instead remains uncharacterized. Biofilm formation of a bacterial consortium consisting of the linuron‐degrading Variovorax sp. WDL1 and metabolite‐degrading strains Comamonas sp. WDL7 and Hyphomicrobium sp. WDL6 at micropollutant linuron concentrations and the impact of auxiliary carbon sources on degradation and biofilm composition were investigated. Biofilms formed at concentrations of 1000, 100, and 10 μg L−1 linuron. The highest biomass, organized in mixed‐species mounds, was observed at 1000 μg L−1 linuron, while at 100 and 10 μg L−1, thin layers of cells occurred. Linuron removal efficiencies decreased from c. 85% when fed with 100 and 1000 μg L−1 linuron to 30% in case of 10 μg L−1 linuron due to reduced specific activity. Biofilms grown on 10 μg L−1 linuron were subsequently fed with easily and less degradable carbon sources in addition to 10 μg L−1 linuron. Although co‐feeding with more degradable C‐sources increased biofilm biomass, linuron removal remained 30%. Calculations based on biofilm volume measurements pointed toward reduced specific activity, compensated by a higher biomass. Uncertainties about biofilm heterogeneity and cell volume can undo this explanation.